1994
DOI: 10.1159/000236600
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transfusion as a Means for Transmission of Retrovirus-Induced Lymphoproliferative Disease in Mice

Abstract: Lymphoproliferative disease was elicited in C57BL/6KH and (BALB/c × C57BL/6)F1 hybrids by a single intraperitoneal injection of 105 FFU of LP-BM5 virus preparation. The disease could reproducibly be transferred by a single intravenous transfusion of 0.2 ml of whole blood as well as 0.1 ml of blood cells, plasma or serum from the infected animals. F1 hybrids displayed a delayed development of the disease when an acellular virus preparation was administered, but they were fully susceptible to the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It has previously been demonstrated that transfer of whole blood, blood cells or plasma from LP-BM5 infected mice can induce MAIDS disease in transfused mice [13]. This suggests that virus is present in the blood in cell-associated and free form.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been demonstrated that transfer of whole blood, blood cells or plasma from LP-BM5 infected mice can induce MAIDS disease in transfused mice [13]. This suggests that virus is present in the blood in cell-associated and free form.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the defective genome, only cells productively coinfected with a helper virus can be quantified by a recently established immunofocus assay using a specific antiserum to the gag p12 portion of the defective virus [17]. The fact that blood can transfer MAIDS [13]and that the ecotropic and MCF virus-infected and infectious cells can be detected in quantities and infection frequencies similar to lymphoid organ suggests that infectious pseudotyped defective virus can also be released by blood cells. As a consequence, virus can use these cells to spread throughout the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation